2013
DOI: 10.1186/1756-3305-6-7
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic filariasis in Papua New Guinea: distribution at district level and impact of mass drug administration, 1980 to 2011

Abstract: BackgroundLymphatic filariasis (LF) caused by Wuchereria bancrofti is present at high prevalence in some parts of Papua New Guinea. However, there has been no rigorous data-based representative assessment of nationwide prevalence of LF. The LF programme has been daunted by the scope of the problem, and progress on mass drug administration (MDA) has been slow and lacking in resources.MethodsA systematic literature review identified LF surveys in Papua New Guinea between 1980 and 2011. Results were extracted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
0
22
0
1
Order By: Relevance
“…As evidenced from the findings of a previous survey, the knowledge gap regarding LF, as well as general attitudes towards and perceptions of the eradication program, was the basis of the major causes of lower compliance [ 28 ], this could have likely resulted in the continued endemicity of LF in the endemic areas of Malaysia. This has been shown to occur in Kenya [ 29 , 30 ], Papua New Guinea [ 31 ], and in India [ 25 , 32 ], where it was reported that there was low compliance for an MDA program due to poor knowledge of LF by the target population. On one hand there is sometimes the problem of poor drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced from the findings of a previous survey, the knowledge gap regarding LF, as well as general attitudes towards and perceptions of the eradication program, was the basis of the major causes of lower compliance [ 28 ], this could have likely resulted in the continued endemicity of LF in the endemic areas of Malaysia. This has been shown to occur in Kenya [ 29 , 30 ], Papua New Guinea [ 31 ], and in India [ 25 , 32 ], where it was reported that there was low compliance for an MDA program due to poor knowledge of LF by the target population. On one hand there is sometimes the problem of poor drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil analisis review di Papua New Guinea mendapatkan bahwa identifikasi pengetahuan, lokasi populasi berisiko dapat digunakan untuk memprediksi pengaruh dari pengobatan massal filariasis sehingga dapat dilakukan penguatan program dan monitoring kegiatan eliminasi filariasis. 18 Faktor lain yang berpengaruh terhadap cakupan pengobatan filariasis adalah jarak ke sarana kesehatan, keberadaan kader, efek samping pengobatan dan monitoring pengobatan.…”
Section: Metodeunclassified
“…There are an estimated 2.7 million cases of LF in Oceania, accounting for 2% of the global disease burden due to this disease, although this figure comes from only one report of national data in PNG [ 10 ]. However, this may be an overestimate as prevalence varies greatly by village and province [ 11 ]. Utilising the Global Program for Elimination of Lymphatic Filariasis (GPELF) criteria, 4.81 million individuals in PNG live in endemic districts [ 11 ].…”
Section: Introductionmentioning
confidence: 99%